The determinants of integrating women and children-friendly village programs with Anti-drug programs and Stakeholder-Based inclusive village programs - Noverman Duadji; Novita Tresiana; Intan Fitri Meutia (Journal of Governance and Accountability Studies, 2023)
Purpose: Considering the recent phenomenon, there has been an increase in the types and sources of village programs, but program implementation often needs improvement. The cause of failure is thought to be that the ministry designed and implemented the program unilaterally, running partially without stakeholder involvement. Therefore, the objectives of this research are (1) to explain stakeholder involvement and (2) to identify critical factors for the success of village program integration. Research methodology: To the research objectives, the method used is a micro-qualitative method through social mapping as an instrument for community development models. Results: The results obtained are research findings, which consist of (a) the village government's initiation through discussion forums succeeded in equalizing stakeholder perceptions and (b) initiation becomes a way for program integration and an arena capable of encouraging the development of program democratization. Limitations: The research limitation is that the research area only covers one village, so the conclusions obtained are micro. The scope of the substance and area must be expanded to obtain a more comprehensive picture and more in-depth formulation of the findings. Contribution: The research explains that program integration supports improving the socio-economic conditions of village communities, strengthening collaboration, sharing resources, responsibility, innovation, and program expansion.